STRATEGI MENGEMBANGKAN KREATIVITAS MAHASISWA DALAM PEMBELAJARAN TATA BUSANA - Weni Nelmira (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
Creativity is an important role in the education of Fashion Education because only creative individuals can produce creative ideas and products. The Fashion Education has to perform its function for the formation of character, work culture, personality, skill, knowledge, behavior and various life skill according to the demands of work world. Fashion Education is still not maximized in developing the creativity of students, especially the ability to think creatively in solving the problems of daily life that it faces. For that required the creativity of educators to foster student creativity. Student creativity will emerge, if the teacher as a pilot in the classroom also has adequate creativity. The subject matter that has been prepared in the syllabus, should be well developed to achieve the predetermined educational objectives. The development of creativity can be done with brainstorming learning, giving motivation, bringing creative people to school and not limit the student excessively by directing students to express and actualize themselves in relation to oneself, to nature, and to others.